The influencing factors of user loyalty on e-commerce shopping guide platform -- Case “Shenmezhidemai” - Yi, Yaqi (My University, 2022)
In recent years, the development of the online retail market has become more and more diversified. There are a large number of advertisements and products gathered on major e-commerce platforms. Consumers cannot efficiently select the products they want in the huge product pool, and it is also difficult for merchants to select high-quality products. The products are precisely oriented to consumers, so the e-commerce shopping guide industry has begun to spread, develop and become popular. To help consumers select high-quality goods more quickly, the e-commerce shopping guide platforms collect and integrate information and discounts for users, and provide users with decision-making suggestions. However, there is a phenomenon that users who are dissatisfied after purchasing a product because of product price reduction, quality problems or logistics problems become angry with the e-commerce shopping guide platform. As a result, users even quit and uninstall the e-commerce shopping guide platform completely. In fact, the result should be the responsibility of the merchant who sells the product. This thesis takes the e-commerce shopping guide platform “Shenmezhidemai” as the re-search object, and uses grounded theory, case study and in-depth interview to carry out this research. First of all, this thesis sorts out the relevant research on e-commerce shopping guide platform and user loyalty, and conducts an overview of the environment, development history and status quo, classification, characteristics and profit model of e-commerce shop-ping guide platform. Secondly, based on grounded theory and in-depth interview method, 20 people participated in the interview, and the interview records of about 20,000 words were obtained. Through open coding, axial coding, selective coding and other processes, the key influencing factors of e-commerce shopping guide platform user loyalty are analyzed and the theoretical model is constructed. Through the eight categories of user-related factors, information utility, system utility, platform reputation, recommending function, interactive function, price comparison function and cross-border shopping function, the model of influencing factors of e-commerce shopping guide platform user loyalty is carefully analyzed. Finally, aiming at the above eight categories, corresponding suggestions are put forward for e-commerce shopping guide platforms to cultivate and increase user loyalty. The thesis hopes to provide some implications and recommendations for the development of e-commerce shopping guide platforms.
Keywords: E-commerce shopping guide platform, User loyalty, Influencing factors, Grounded theory